2014
DOI: 10.4049/jimmunol.1302196
|View full text |Cite
|
Sign up to set email alerts
|

Rab5 Is a Novel Regulator of Mast Cell Secretory Granules: Impact on Size, Cargo, and Exocytosis

Abstract: Secretion of inflammatory mediators prestored in mast cells secretory granules (SGs) enhances immune responses such as in allergy and host defense. However, the mechanisms underlying the biogenesis of the SGs remain largely unresolved. By combining high-resolution live cell imaging and quantitative morphometric analyses, we show that the small GTPase Rab5 controls the SG size and cargo composition by a VAMP8-dependent fusion mechanism. Knockdown of the endogenous Rab5, or expression of constitutively negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 70 publications
(85 reference statements)
4
61
0
Order By: Relevance
“…This mechanism would provide reliable communication machinery for adaptation to environmental insults. Increases in Ca 2+ i and its sensor for vesicle fusion, synaptotagmin, are required for compound fusion (55) and other proteins such as Rab5 and VAMP8, are known to play a role in homotypic secretory granule fusion in MC (56).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism would provide reliable communication machinery for adaptation to environmental insults. Increases in Ca 2+ i and its sensor for vesicle fusion, synaptotagmin, are required for compound fusion (55) and other proteins such as Rab5 and VAMP8, are known to play a role in homotypic secretory granule fusion in MC (56).…”
Section: Discussionmentioning
confidence: 99%
“…The inverse relationship between the number and size of SGs suggested that Rab5-mediated homotypic fusion of the SGs. Indeed, high-resolution imaging of the giant SGs by confocal microscopy of living cells, which detected Rab5A decorating fusing SGs, and electron micrographs that depicted considerably larger SGs and homotypic fusion between two or more granules in CA Rab5A-expressing cells, have reinforced this conclusion (Azouz et al, 2014). The interaction of Rab5 with the SGs was transient and occurred shortly after their Golgi exit (Azouz et al, 2014).…”
Section: Rab5 Controls Sg Fusionmentioning
confidence: 94%
“…Among the Rabs that displayed a remarkable phenotypic impact, we identified Rab5 as a regulator of SG fusion (Azouz et al, 2014). Coexpression of constitutively negative GDP-locked mutants of the endogenously expressed isoforms of Rab5 (Rab5A, Rab5B, and Rab5C) or expression of Rab5A/B/C targeting shRNAs, reduced significantly the SGs' size with a concomitant increase in their numbers (Azouz et al, 2014).…”
Section: Rab5 Controls Sg Fusionmentioning
confidence: 99%
See 2 more Smart Citations